Laboratory-Based Factors Predicting Skiing Performance in Female and Male Biathletes - Laaksonen, Marko S.; Andersson, Erik; Jonsson Kårström, Malin; Lindblom, Hampus; McGawley, Kerry (Frontiers in Sports and Active Living, 2020)
Skiing in biathlon is a high-intensity, intermittent endurance discipline. This study aimed to evaluate the relationships between laboratory-derived physiological variables and skiing performance during a field-based biathlon competition (BC) for female and male biathletes. Fourteen female (23 ± 3 yr, VO2max 56 ± 4 mL kg-1 min-1) and 14 male (24 ± 4 yr, VO2max 66 ± 3 mL kg-1 min-1) biathletes performed a submaximal incremental test and a maximal time-trial (TT) using treadmill roller-skiing for the assessment of oxygen uptake at a lactate threshold of 4 mmol L-1 (V ̇O2@4mmol), gross efficiency (GE), aerobic (MRae) and anaerobic (MRan) metabolic rates, peak oxygen consumption (V ̇O2peak), anaerobic capacity and TT performance. Field-based skiing performance was assessed during a BC. The TT and BC skiing performances were significantly correlated in both sexes (r = 0.68–0.69, p < 0.01). VO2peak (31/21 %), anaerobic capacity (1/0 %), and GE (35/32 %) explained 67 % and 52 % of the variance in BC skiing performance for the females (p < 0.01) and males (p = 0.051), respectively. A second model showed that VO2@4mmol (30/35 %), anaerobic capacity (0/0 %) and GE (37/13 %) explained 67 % and 48 % of the variance in BC skiing performance for the females (p < 0.01) and males (p = 0.077), respectively. Results of this study suggest that a high VO2@4mmol and GE, but not anaerobic capacity, are important for BC skiing performance, especially for females. In addition, a laboratory-based TT could be useful for regular laboratory testing of biathletes due to its relationship with field-based skiing performance in biathlon.